Pengendalian Kualitas Produk Cacat Hollow Alumunium Menggunakan Metode Six Sigma dengan Tahapan DMAIC (Studi Kasus di PT. XYZ Surabaya) - Dhedy Yuswandi; Anindya Rachma Dwicahyani (Institut Teknologi Adhi Tama Surabaya, 2021)
PT. XYZ is a manufacturing company that produces various aluminum products, such as truss, battens, hollow and galvalume. In order to improve and control product quality and minimize product defects, the first step that companies need to do is to find the root of any problems regarding product quality that do not meet specifications. In this study, an analysis of hollow product quality control was carried out using the six sigma method under DMAIC (define, measure, analyze, improve, control) stages to reduce defective products. Six sigma is a quality control method that pays more attention to the creation of high quality products with the smallest possible defect rate. The results showed that there were three types of product defects, namely detached clamp, eroded material and some wavy parts. From the DPMO and sigma calculation of hollow product, it is known that the average level of DPMO is 20,615 and sigma value is 3.6.